1991
DOI: 10.1021/j100177a013
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of long-range Coulomb interactions to bimolecular luminescence quenching reactions

Abstract: 9660J . Phys. Chem. 1991. 95, 9660-9666 flexible molecules. However, the resolution obtained from a single measurement can be modest (see xR2 surfaces for single files) and estimated values of the recovered parameters can be questionable. Beechem and H a d have recently discussed this problem for time-domain measurements and suggested simultaneous analysis of the donor and acceptor decay kinetics. This type of global analysis is potentially valuable and intuitively obvious, but is very difficult to realize in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…Taken in conjunction with the Stern-Volmer constant, the electrontransfer rate constant is between 8 × 10 6 and 3 × 10 8 M −1 s −1 . This rate constant compares favorably with those reported elsewhere for ruthenium polypyridyl complexes in solution, solids and thin films [56][57][58][59][60]. However, when describing lateral quenching it is more appropriate to consider the process as occurring in twodimensional space.…”
Section: Lateral Quenchingsupporting
confidence: 82%
“…Taken in conjunction with the Stern-Volmer constant, the electrontransfer rate constant is between 8 × 10 6 and 3 × 10 8 M −1 s −1 . This rate constant compares favorably with those reported elsewhere for ruthenium polypyridyl complexes in solution, solids and thin films [56][57][58][59][60]. However, when describing lateral quenching it is more appropriate to consider the process as occurring in twodimensional space.…”
Section: Lateral Quenchingsupporting
confidence: 82%
“…As shown in Figure , the parabolic dependence predicted by eq 1 is truncated by the diffusion limit. Consequently, the observed rate constants of most bimolecular reactions display an increase with increasing free energy followed by a leveling at the diffusional limit. Typically, the driving forces of bimolecular ET reactions have not been sufficiently energetic to permit the ET rates to lie outside the diffusion limit. Pioneering studies by Sutin and Creutz reported “vestiges” of the inverted region for the bimolecular reactions of metal polypyridyl complexes, and the inverted region has been indirectly inferred from chemiluminescent bimolecular reactions. , Direct observation of inverted region behavior for a bimolecular reaction has only recently been achieved by Gray and co-workers in their studies of the back reaction between the products resulting from the quenching of an electronically excited binuclear iridium complex by pyridinium acceptors …”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that the face-bridging ligands decisively influence the emission maxima; luminescence parameters of clusters having the same bridging ligand gravitate together in Figure 2; the E em values of the [W 6 I 8 X' 6 ] 2À clusters are identical within experimental error at 21 AE 2 8C in acetonitrile.Alongside the luminescence lifetimes, other experimental evidence suggests emission from a spin-triplet excited state. Tungsten(II) halide cluster emission undergoes bimolecular quenching both oxidatively and by energy-transfer mechanisms; [37,[48][49][50] molybdenum analogues are quenched both oxidatively and reductively, and by energy transfer. 57] The luminescence quenching property of [Mo 6 Cl 14 ] 2À has been applied in the building of a fiber-optic oxygen sensor active at partial pressures encountered in automotive and biological applications, and having a theoretical response time of 1 s. [58] Quantum-chemical characterization specifically of the tungsten(II) halide clusters is sparse.…”
mentioning
confidence: 99%